Pengaruh Hubungan Teman Sebaya dan Kondisi Sosial Ekonomi Keluarga Terhadap Orientasi Karir - Gunawan, Yusuf Rudy (Indonesian Journal of Guidance and Counseling: Theory and Application, 2017)
This research is based on data obtained in five high school districts throughout the country Purbalingga that the number of students who go on to college or work after graduation by 30% -50%. The purpose of this research to determine the effect of peer relationships and socio-economic conditions of the students career orientation. This research is a survey research data analysis used is simple regression analysis and multiple linear regression analysis. The research instrument in the form of questionnaires. The population is all the high school students throughout the country Purbalingga district by 6629 the number of students and cluster proportional sample using random sampling so that the number of research subjects were 142 students. Hypothesis test uses multiple linear regression analysis, test results obtained coefficient of determination (R2) of 0.790, which means that Ha accepted and Ho rejected. The results showed that peer relationships and socio-economic conditions of the students career orientation.